Community Structure and Toxicity Potential of Cyanobacteria during Summer and Winter in a Temperate-Zone Lake Susceptible to Phytoplankton Blooms - Wejnerowski, Łukasz; Dulić, Tamara; Akter, Sultana; Font-Nájera, Arnoldo; Rybak, Michał; Kamiński, Oskar; Czerepska, Anna; Dziuba, Marcin K.; Jurczak, Tomasz; Meriluoto, Jussi; Mankiewicz-Boczek, Joanna; Kokociński, Mikołaj (MPDI, 2025)
Cyanobacterial blooms are increasingly common during winters, especially when they are mild. The goal of this study was to determine the summer and winter phytoplankton community structure, cyanotoxin presence, and toxigenicity in a eutrophic lake susceptible to cyanobacterial blooms throughout the year, using classical microscopy, an analysis of toxic cyanometabolites, and an analysis of genes involved in biosynthesis of cyanotoxins. We also assessed whether cyanobacterial diversity in the studied lake has changed compared to what was reported in previous reports conducted several years ago. Moreover, the bloom-forming cyanobacterial strains were isolated from the lake and screened for cyanotoxin presence and toxigenicity. Cyanobacteria were the main component of the phytoplankton community in both sampling times, and, in particular, Oscillatoriales were predominant in both summer (Planktothrix/Limnothrix) and winter (Limnothrix) sampling. Compared to the winter community, the summer community was denser; richer in species; and contained alien and invasive Nostocales, including Sphaerospermopsis aphanizomenoides, Raphidiopsis raciborskii, and Raphidiopsis mediterranea. In both sampling times, the blooms contained toxigenic species with genetic determinants for the production of cylindrospermopsin and microcystins. Toxicological screening revealed the presence of microcystins in the lake in summer but no cyanotoxins in the winter period of sampling. However, several cyanobacterial strains isolated from the lake during winter and summer produced anabaenopeptins and microcystins. This study indicates that summer and winter blooms of cyanobacteria in the temperate zone can differ in biomass, structure, and toxicity, and that the toxic hazards associated with cyanobacterial blooms may potentially exist during winter.